Sistem Deteksi Kawasan Bebas Rokok Dengan Menggunakan Sensor MQ-7 Berbasis Raspberry PI - Sudarman, Asa Arya; Linawati, Linawati; Wirastuti, Ni Made Ary Esta Dewi (Majalah Ilmiah Teknologi Elektro, 2018)
This paper proposes a smoke detection tool that will be used to find out who will smoke in the classroom environment on campus.Implementation of the system smoker detector using Raspberry PI, sensor, webcam and also motor servo. Sensor that been used on the System to detect smoke from the cigarette is MQ-7, which is detect the ratio of Carbon Monocside (CO) on the smoke. If the system detecting the cigarette, camera of the system will be headed to source of the smoke, capture the subject and then send the photo into telegram through the API using wifi connection. After the university side will monitoring the system and handle the subject whom breaking the rules due to smoking in the campus area is not allowed. The result of the experiment is the system which designed for smoke detector can detect the source of smoke is going well and appropriate regard on the scenario and functionality design. From the results of the prototype, the prototype can detect the smoke that come from cigarettes according the location. The experiment on indoor area show the success level is get almost most value within 15 second and an average distance 300 cm. For result above 400cm get results below 50%.